Perubahan Tata Cara Perkawinan Suku Anak Dalam (Studi Kasus: Suku Anak Dalam di Provinsi Jambi) - Gustiya Ulfah (Universitas Merdeka Malang, 2024)
The aim of the research is to find out more about the existence of the Anak Dalam Tribe and the changes that have occurred in marriage procedures. The descriptive qualitative research method involves key informants and casual informants. Data collection was carried out by observation, interviews and literature study. Analysis of research data was taken from observations and interviews. The changes to the Anak Dalam tribe's marriages include changes to the process which was initially closed and could only be seen by that group, now marriages can be seen by the general public. Factors influencing changes in marriage include modernization and globalization, education, interaction with the majority culture, and economic changes. In addition, beliefs that are believed to guide life are replaced by religion which has an impact on changes in family structure, gender, foreign culture and cultural identity.